Optimalisasi Layanan Perpustakaan dalam Meningkatkan Minat baca Siswa - Moch Basit Aulawi (IAIN Ponorogo, 2012)
The key to use a knowledge treasury on library especially school library is reading. And the process of reading a literature will be maximal if it is done by interest in reading. In addition to having main duty, such as information, circulation and reference service, school library has a role to increase interest in reading of students. A lot of services of library to increase student's interest in reading are those which become part of learning process, service to increase student's skill to explore information, and service to increase library use. So, the library many oppotunities to increase student's interest in reading. The main parts, especially librarian. Those process will form a paradigm the reading is the main matter in learning process. This essay will explore library's role to increase student's interest in reading.